Chronic Ethanol Administration Prevents Compensatory Cardiac Hypertrophy in Pressure Overload. (13th June 2018) - Ninh, Van K.; El Hajj, Elia C.; Mouton, Alan J.; El Hajj, Milad C.; Gilpin, Nicholas W.; Gardner, Jason D.
Abstract : Background: Alcohol is among the most commonly abused drugs worldwide and affects many organ systems, including the heart. Alcoholic cardiomyopathy is characterized by a dilated cardiac phenotype with extensive hypertrophy and extracellular matrix (ECM) remodeling. We have previously shown that chronic ethanol (EtOH) administration accelerates the progression to heart failure in a rat model of volume overload. However, the mechanism by which this decompensation occurs is unknown. For this study, we hypothesized that chronic EtOH administration would prevent compensatory hypertrophy and cardiac remodeling in a rodent model of pressure overload (PO). Methods: Abdominal aortic constriction was used to create PO in 8‐week‐old male Wistar rats. Alcohol administration was performed via chronic intermittent EtOH vapor inhalation for 2 weeks prior to surgery and for the duration of the 8‐week study. Echocardiography measurements were taken to assess ventricular functional and structural changes. Results: PO increased posterior wall thickness and the hypertrophic markers, atrial and B‐type natriuretic peptides (ANP and BNP). With the added stressor of EtOH, wall thickness, ANP, and BNP decreased in PO animals. The combination of PO and EtOH resulted in increased wall stress compared to PO alone. PO also caused increased expression of collagen I and III, whereas EtOH alone only increased collagen III. The combined stresses of PO and EtOH led to an increase in collagen I expression, but collagen III did not change, resulting in an increased collagen I/III ratio in the PO rats treated with EtOH. Lastly, Notch1 expression was significantly increased only in the PO rats treated with EtOH. Conclusions: Our data indicate that chronic EtOH may limit the cardiac hypertrophy induced by PO which may be associated with a Notch1 mechanism, resulting in increased wall stress and altered ECM profile. Abstract : Pressure overload induces cardiac remodeling, which include hypertrophic and profibrotic changes in the heart. These compensatory changes serve to preserve and maintain cardiac function in the face of adverse stimuli. However, chronic ethanol administration increased fibrosis and reduced the ability of the heart to undergo hypertrophy. These changes were associated with altered Notch1 signaling. We conclude that ethanol disrupts the heart's natural ability to compensate to pressure overload, which may accelerate the progression to heart failure.